Optimizing Methane Production from Anaerobic Digestion of Dairy Cow Manure: The Potential Use of Carica (Carica pubescens) Seeds as a Co-Substrate - Purwasih, R.; Saindah, M.; Triyuwanti, H.; Yusuf, F. S.; Purnomoadi, A.; Purbowati, E.; Sutaryo, S. (Tropical Animal Science Journal, 2025)
A method to increase methane production in dairy cow manure (DCM) is to co-digest DCM with nutritious biomass. This study aimed to determine the methane yield during the anaerobic co-digestion of DCM and carica seeds meal (CSM). Four continuous stirred tank reactors were operated with treatments P0 (100% DCM), P1 (98% DCM and 2% CSM), P2 (96% DCM and 4% CSM), and P3 (94% DCM and 6% CSM). The results demonstrated that the presence of CSM as a co-substrate of DCM significantly increased (p